Dysregulated FOXM1 signaling in the regulation of cancer stem cells - Gulab Sher (12984698) (2022)
Since the introduction of the cancer stem cell (CSC) paradigm, significant advances have been made in understanding the functional and biological plasticity of these elusive components in malignancies. Endowed with self-renewing abilities and multilineage differentiation potential, CSCs have emerged as cellular drivers of virtually all facets of tumor biology, including metastasis, tumor recurrence/relapse, and drug resistance. The functional and biological characteristics of CSCs, such as self-renewal, cell fate decisions, survival, proliferation, and differentiation are regulated by an array of extracellular factors, signaling pathways, and pluripotent transcriptional factors. Besides the well-characterized regulatory role of transcription factors OCT4, SOX2, NANOG, KLF4, and MYC in CSCs, evidence for the central role of Forkhead box transcription factor FOXM1 in the establishment, maintenance, and functions of CSCs is accumulating. Conventionally identified as a master regulator of the cell cycle, a comprehensive understanding of this molecule has revealed its multifarious oncogenic potential and uncovered its role in angiogenesis, invasion, migration, self-renewal, and drug resistance. This review compiles the large body of literature that has accumulated in recent years that provides evidence for the mechanisms by which FOXM1 expression promotes stemness in glioblastoma, breast, colon, ovarian, lung, hepatic, and pancreatic carcinomas. We have also compiled the data showing the association of stem cell mediators with FOXM1 using TCGA mRNA expression data. Further, the prognostic importance of FOXM1 and other stem cell markers is presented. The delineation of FOXM1-mediated regulation of CSCs can aid in the development of molecularly targeted pharmacological approaches directed at the selective eradication of CSCs in several human malignancies. Other Information Published in: Seminars in Cancer Biology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.semcancer.2022.07.009